The Effectiveness of Post-operative Analgesia in Caesarean Section Patients at King Dinuzulu Hospital Complex: A Prospective Qualitative Descriptive analytical study at a District level Hospital in South Africa. - Curtis, Tatum; Singaram, Shree (Student's Journal of Health Research Africa, 2025)
Background: Post-operative pain management in caesarean section (C-section) patients is crucial for optimal recovery. However, pain control in district-level hospitals, such as King Dinuzulu Hospital Complex in KwaZulu-Natal, often faces challenges due to resource limitations and variability in clinical practices. The study aimed to assess post-operative pain management following spinal anaesthesia in women receiving a caesarean section. The main objective was to assess a patient's pain level at specified time intervals post-operatively – therefore evaluating the adequacy of the post-operative analgesia prescribed and administered in decreasing a patient’s pain level. Methods: This prospective qualitative descriptive analytical study included 157 women undergoing elective C-sections under spinal anesthesia. Pain management effectiveness was assessed using patient questionnaires and visual analogue scales (VAS) at multiple time points post-operation. Results: The participants ranged in age from 18 to 44 years with a mean age of 30.5 years (SD = 5.54) and most of the participants were African (96.1%). The study revealed significant variability in analgesic prescriptions and administration, with many patients experiencing suboptimal pain relief. Despite a standard protocol, 29.9% of patients reported increased pain 24 hours post-surgery, highlighting inconsistencies in pain management practices. Conclusion: The findings underscore the need for standardized pain management protocols and improved training for healthcare providers to enhance patient outcomes. Recommendations The Authors recommend that healthcare workers should be trained on the latest postoperative analgesia guidelines for women coming for caesarean section. Pain should be regularly assessed in the postnatal ward and analgesia administered timeously.